2022
DOI: 10.1177/21582440221079847
|View full text |Cite
|
Sign up to set email alerts
|

Causes of Undergraduate Students’ Underachievement in a Gulf Cooperation Council Country (GCC) University

Abstract: UNESCO reports enrollment in higher education in the Arab and Gulf Cooperation Council region doubled from 5.1 million in 2000 to 10.7 million in 2015. Despite significant budgets and the world’s lowest teacher-to-student ratio, higher education in this region is plagued by student underachievement. This study identifies academic underachievement factors among undergraduate students at risk at a national university in the GCC. As part of the Intrusive Intervention Program, students were required to complete an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Much of the effort in the teaching and learning processes are devoted to the student's taking and successfully passing the written examination. Teacher's disregard of performance-based and authentic assessment tasks results to student's lack of competence and underachievement (Johnson, 2022).…”
Section: Heavy Reliance On Conventional Teaching-learning Activities ...mentioning
confidence: 99%
“…Much of the effort in the teaching and learning processes are devoted to the student's taking and successfully passing the written examination. Teacher's disregard of performance-based and authentic assessment tasks results to student's lack of competence and underachievement (Johnson, 2022).…”
Section: Heavy Reliance On Conventional Teaching-learning Activities ...mentioning
confidence: 99%
“…Colleges should also strive to raise awareness about the impact of social problems on students' mental health and academic performance to destigmatize seeking help and encourage students to access available resources [6]. Implementing these recommendations can contribute to a positive academic experience, enhance student retention rates, and foster a supportive and thriving learning community [10][11][12][13][14][15].…”
Section: Academic Recommendationsmentioning
confidence: 99%
“…Also, in order to choose his studies and career in all of his confluences of existence with the shared concern of serving society and the development of his responsibilities, an individual must first become aware of his characteristics and develop them [22,23]. The findings by Johnson et al [24] reported that students believed that academic issues were the most frequent causes of academic underachievement, while social adjustment causes were discovered to be the least frequent.…”
mentioning
confidence: 99%